State space modeling of a BUCK converter and designing a controller - Ahmed, Shaik Raju; Noor, Nusrat Jahan; Mostafa, Sumaiya (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.